EDUCATIONAL INTERVENTION ON NURSES’ USE OF CLINICAL GUIDELINE INDICATORS IN TRACHEOSTOMY CARE IN FEDERAL TEACHING HOSPITALS IN SOUTH-WEST NIGERIA (2018)
Quality nursing decisions in tracheostomy care are guided by clinical indicators and research evidence. Application of these clinical indicators lessen noisy respirations, excessive coughing, skin maceration and infection. Studies showed that tracheostomy care decisions in some clinical settings are not guided by evidence-based clinical indicators. Research findings suggest poor knowledge and utilisation of recommended clinical indicators in tracheostomy care in Nigeria. This study was designed to examine nurses’ knowledge and determine effect of use of clinical guideline indicators in evidence-based tracheostomy care decisions. This Quasi-experimental study was conducted in three Federal Teaching Hospitals in South-West Nigeria: University College Hospital (UCH), Lagos University Teaching Hospital (LUTH), Obafemi Awolowo University Teaching Hospital Complex (OAUTHC). Specific units included were Intensive Care, Neurology, and Ear, Nose and Throat. Due to limited number of nurses, LUTH and OAUTHC were purposely labelled control group (CG), and UCH intervention group (IG). All the 121 nurses in the units were recruited. Data were collected using validated structured decision-making and documentation checklists (inter-observer reliability 0.75-1.0 and 0.76-1.0), and questionnaire (Cronbach’s Alpha Coefficient 0.8 and 0.83). Stage 1 involved participant observation of nurses’ utilisation of clinical indicators for 10 evidence-based tracheostomy assessment, care, and documentation practices per participant in each of; suctioning, airway maintenance, dressing, and tie change decisions in both groups. In stage 2, pre intervention knowledge was assessed in both groups. Educational intervention of five modules on clinical guideline indicators, assessment, care, and documentation of evidence-based tracheostomy care decisions was conducted only in the IG. Knowledge was assessed immediately post intervention in both groups. At 3 months post intervention (stage 3), only participant observation of 10 evidence-based care decisions per participant was conducted as in stage 1 in both groups. Data were analysed using Chi-square, Independent t-test and Mann-Whitney U at α0.05. Sixty-seven of 121 nurses completed the three stages (IG=32; CG=35). There was significant difference in mean knowledge of evidence-based tracheostomy care at pre-test (IG:20.3±3.1; CG:22.0±4.6); which increased in both groups at post-test (IG:31.3±3.3; CG:22.9±3.9). The mean knowledge of decision-making was comparable at pre-test (IG:5.6±1.7; CG:5.5±2.0); but increased at post-test (IG:6.7±1.3; CG:5.9±1.1) in both groups. The mean knowledge of use of clinical guidelines was similar at pre-test (IG:3.0±0.9; CG:3.1±1.1) and post-test (IG:3.2±0.9; CG:3.1±0.91). There was no significant difference in nurses’ performance of evidence-based tracheostomy suctioning assessment decisions: medianpre (IG:5.0; CG:45.0); medianpost (IG:0.0; CG:20.0), suctioning care decisions: medianpre (IG:4.0; CG:32.0); medianpost (IG:0.0; CG:20.0), and airway maintenance care decisions: medianpre (IG:86.6; CG:0.0); medianpost (IG:63.6; CG:50.0). Nurses’ performance of documentation of evidence-based decision-making practices in tracheostomy assessment and care decisions for suctioning, airway maintenance, dressing, and tie change were also not significant in IG and CG, pre and post intervention. Despite the educational intervention there is poor application of clinical guideline indicators to direct evidence-based tracheostomy care decisions and documentation amongst nurses. There is need for regular audit and continuous monitoring of nurses’ decision-making, and periodic research-based continuing education in practice to improve nurses’ clinical competence of evidence-based decision-making, in tracheostomy care.